2015
DOI: 10.3390/ijms160920100
|View full text |Cite
|
Sign up to set email alerts
|

AGEs-Induced IL-6 Synthesis Precedes RAGE Up-Regulation in HEK 293 Cells: An Alternative Inflammatory Mechanism?

Abstract: Advanced glycation end products (AGEs) can activate the inflammatory pathways involved in diabetic nephropathy. Understanding these molecular pathways could contribute to therapeutic strategies for diabetes complications. We evaluated the modulation of inflammatory and oxidative markers, as well as the protective mechanisms employed by human embryonic kidney cells (HEK 293) upon exposure to 200 μg/mL bovine serum albumine (BSA) or AGEs–BSA for 12, 24 and 48 h. The mRNA and protein expression levels of AGEs rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
0
15
0
5
Order By: Relevance
“…This difference between the two inflammatory pathways was evident during the 6-12 hour period of treatment (T1) with sRAGE being lower in comparison to the rapid increase in the majority of cytokines, possibly initiated by insulin treatment (4,5,8,9). While interactions between components of the two pathways are likely (37,38,39), we were unable to confirm interactions in this study. Of interest, we also noted a difference in sRAGE concentrations at three months post-DKA therapy by ethnicity and gender with C having significantly higher (p=0.003) sRAGE concentrations compared with AA and this concentration was also significantly higher (p=0.04) in females than males.…”
Section: Discussionmentioning
confidence: 63%
“…This difference between the two inflammatory pathways was evident during the 6-12 hour period of treatment (T1) with sRAGE being lower in comparison to the rapid increase in the majority of cytokines, possibly initiated by insulin treatment (4,5,8,9). While interactions between components of the two pathways are likely (37,38,39), we were unable to confirm interactions in this study. Of interest, we also noted a difference in sRAGE concentrations at three months post-DKA therapy by ethnicity and gender with C having significantly higher (p=0.003) sRAGE concentrations compared with AA and this concentration was also significantly higher (p=0.04) in females than males.…”
Section: Discussionmentioning
confidence: 63%
“…The characteristic fluorescence emission spectra of glycation products were assessed at λEx/Em = 335 nm/ 385 nm (pentosidine fluorescence) and λEx/Em = 340 nm/ 370 nm (AGEs fluorescence) and revealed significant increases at both excitation/emission wavelengths by 3 and 2.25 fold compared to unmodified BSA. The total AGEs content was evaluated using an ELISA assay (Advanced Glycation End Product ELISA Kit, Cell Biolabs, San Diego, CA, USA) which revealed that the glycated products content in AGEs-BSA increased by 3.2 fold compared to BSA, reaching 4.8 ng/μg protein [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cell membrane fractions were obtained using the RedyPrep Protein Extraction Kit (Bio-Rad Laboratories, Hercules, CA, USA) according to manufacturer’s instructions, and modified as previously described [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conditioned media samples with a total protein concentration of 800 μg/mL were used for the detection of secreted IL-2, IL-4, IL-6, IL-8, IL-10, GM-CSF, IFN-γ and TNF-α cytokines using a Bio-Plex Pro Human Cytokine 8-plex panel (Bio-Rad), as previously described 10 . Secreted IL-1β was separately quantified using Bio-Plex Pro Human Cytokine Standard 27-plex, Group I, magnetic beads and detection antibodies for human IL-1β (Bio-Rad).…”
Section: Quantification Of Inflammatory Cytokines and Mmps From Concementioning
confidence: 99%